2018
DOI: 10.1007/s00167-018-5035-y
|View full text |Cite
|
Sign up to set email alerts
|

Posterior laxity increases over time after PCL reconstruction

Abstract: Cohort study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“…Based on our own clinical findings, we believe that a slope increasing anterior open wedge osteotomy offers an additional powerful tool to further improve outcome after PCL reconstruction in this subset of patients. 27,28 Even though Bernhardson et al have reported on conflicting results about the influence of slope on outcome after PCL reconstruction as compared with our results, 23 we are still encouraged to follow our approach with a larger group of patients and a longer follow-up. However, in contrast to ACL surgery, a clear threshold at which degree of tibial slope, a sole slope increasing osteotomy is indicated, needs to be further defined.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on our own clinical findings, we believe that a slope increasing anterior open wedge osteotomy offers an additional powerful tool to further improve outcome after PCL reconstruction in this subset of patients. 27,28 Even though Bernhardson et al have reported on conflicting results about the influence of slope on outcome after PCL reconstruction as compared with our results, 23 we are still encouraged to follow our approach with a larger group of patients and a longer follow-up. However, in contrast to ACL surgery, a clear threshold at which degree of tibial slope, a sole slope increasing osteotomy is indicated, needs to be further defined.…”
Section: Discussionmentioning
confidence: 71%
“…27 Hereinafter, Gwinner et al advocated in 2018 that there is a significant stretch out of PCL reconstructions, as measured in serial stress-radiographs, if the tibial slope deceeds 8 degrees. 28 Furthermore, Bernhardson et al demonstrated that in a population of PCL injured knees, the slope was significantly lower as compared with an uninjured control population. 29 By implication, there is a growing body of clinical as well as biomechanical evidence that in patients with a markedly reduced tibial slope, a slope increasing, or flexion osteotomy might be considered prior to PCL reconstruction, especially in revision cases (►Fig.…”
mentioning
confidence: 99%
“…First, it evaluated only radiographic PTT because clinical outcomes scores, such as the Lysholm or Western Ontario and McMaster Universities Osteoarthritis Index score, were not fully available in several cases from the medical records. Second, the PTT was evaluated only in the gravity sag view without comparing a stress radiograph using a Telos device (Telos GmbH) 11 , 12 or with a kneeling technique 19 or comparing the posterior laxity with the KT knee arthrometer (MEDmetric) 1 , 48 ; notably, the posterior tibial load in the gravity sag view, generated by individual patients’ shank weights, could be smaller than those on stress radiographs. A higher BMI with a higher shank weight was also potentially associated with the nonsignificantly larger postoperative PTT.…”
Section: Discussionmentioning
confidence: 99%
“…The current study therefore aimed to investigate sequential changes in the radiographic PTT through PCLR and analyze the risk factors that influence the onset of postoperative residual posterior sagging. It was hypothesized that the PTT would recur in the early postoperative period but not proceed thereafter and that some risk factors, such as a smaller posterior tibial slope, 11 , 12 could affect the postoperative residual PTT.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] Although these techniques can achieve minimal posterior translation intraoperatively, joint laxity may recur insidiously after surgery. In a cohort of 46 patients, Gwinner et al 7 showed that, although laxity was improved at 3 months after PCL reconstruction, posterior tibial translation significantly recurred at a final follow-up of 5 years. Loss of stability is thought to be due to sagging of the tibia disturbing the graft during incorporation and possible disruption of the graft at the "killer turn."…”
mentioning
confidence: 99%